Prevalence and ultrasound patterns of testicular adrenal rest tumors in adults with congenital adrenal hyperplasia - Corcioni, Beniamino (Transl Androl Urol, 2021)
BACKGROUND: Testicular adrenal rest tumors (TARTs) are benign neoplasms affecting patients with congenital adrenal hyperplasia (CAH). The prevalence of TART in adult patients with CAH is not well known. Ultrasonography (US) is the main tool for diagnosing TART and the role of contrast-enhanced US (CEUS) is never investigated. The aim of this study was to evaluate the TART prevalence in adults with CAH, by stratifying patients according to disease phenotype and assessing the diagnostic performance of US, color Doppler (CD) US and CEUS. METHODS: Male patients >16 years old with certain diagnosis of CAH who underwent US for TARTs, between December 2015 and September 2019 were prospectively enrolled. The control group included patients without CAH affected by testicular lesions at US other than TARTs. RESULTS: TARTs were identified in 16 of 52 patients (31%), of whom 15 (93.8%) displayed the salt-wasting (SW) form (P<0.001). The prevalence of TARTs in patients with the SW form was 54%. One patient with the non-classic (NC) form (6%) showed TART (likely the first documented case). The mean age of patients upon detection of TARTs was significantly younger compared with the control group (P<0.001); moreover, TARTs were bilateral in 15/16 patients (93.8%; P<0.001) and the largest lesion was more frequent in the medium third of testis in the TART group (87.5%), statistically different from the control group (P=0.013). CONCLUSIONS: TARTs almost exclusively affected patients with the SW form of CAH. Age at diagnosis and bilateralism are useful factors for achieving a correct diagnosis of TARTs in CAH adult patients.